The complete short stories - Poe, Edgar Allan, 1809-1849 (MysteriousPress.com/Open Road Integrated Media, 2014)
Surreal tales of suspense and imagination from an American masterThe Complete Short Stories is the ultimate collection of Edgar Allan Poe's tales of the macabre--from the world-famous classics?The Tell-Tale Heart,??The Pit and the Pendulum,? and?The Cask of the Amontillado? to lesser-known masterpieces such as?The System of Doctor Tarr and Professor Fether? and?The Devil in the Belfry.? Fans of Poe's Gothic tales of horror will thrill to discover his brilliant French detective, C. Auguste Dupin. Readers familiar with Poe's mysteries will find new pleasure in his dark comedy and early science fiction stories. Edgar Allan Poe was one of the most brilliant and influential authors in American history, and The Complete Short Stories is a must-have for every admirer of his work. This ebook has been professionally proofread to ensure accuracy and readability on all devices.